2010
DOI: 10.1002/rob.20344
|View full text |Cite
|
Sign up to set email alerts
|

Vision‐based autonomous convoying with constant time delay

Abstract: This paper describes the design and experimental validation of a vision-based vehicle-following system that uses only onboard sensors to enable a convoy of follower vehicles to autonomously track the trajectory of a manually driven lead vehicle. The tracking is done using the concept of a constant time delay, in which a follower tracks the delayed trajectory of its leader. This constant-time-delay approach allows for new techniques to be used to estimate the speed and heading of the leader. Experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Convoy systems that are string stable will show spacing errors that decrease along the follower vehicles ( Li and He, 2018 ; Rödönyi et al, 2014 ; Gáspár et al, 2014; Bokor and Palkovics, 2014; Liu et al, 2014 ; Gao et al, 2014; Xu et al, 2014; Liu and Cheng, 2014; Gong et al, 2016 ; Shen and Du, 2016), as shown on the left side of Figure 3B . A separate way that spacing error is commonly used is in comparing convoy member vehicle offset to the desired trajectory, which is known as path following error ( Klančar et al, 2011 ; Zhao et al, 2017 ; Goi et al, 2010 ; Klančar et al, 2009) , as shown on the right side of Figure 3B . The path offset is then used to calculate an error metric, such as with a root mean squared error approach.…”
Section: Manned Convoy Requirementsmentioning
confidence: 99%
“…Convoy systems that are string stable will show spacing errors that decrease along the follower vehicles ( Li and He, 2018 ; Rödönyi et al, 2014 ; Gáspár et al, 2014; Bokor and Palkovics, 2014; Liu et al, 2014 ; Gao et al, 2014; Xu et al, 2014; Liu and Cheng, 2014; Gong et al, 2016 ; Shen and Du, 2016), as shown on the left side of Figure 3B . A separate way that spacing error is commonly used is in comparing convoy member vehicle offset to the desired trajectory, which is known as path following error ( Klančar et al, 2011 ; Zhao et al, 2017 ; Goi et al, 2010 ; Klančar et al, 2009) , as shown on the right side of Figure 3B . The path offset is then used to calculate an error metric, such as with a root mean squared error approach.…”
Section: Manned Convoy Requirementsmentioning
confidence: 99%
“…On the other hand, there could even be negative effects within the type of upper costs in traveling distances for service personal. Additionally, Goi [22] analyzed the results of automation on machinery sizes and costs for soil tillage and crop establishment [23]. He assumed that the ratios between an autonomous tractor and a manned tractor, in terms of price, labor requirement and daily working hours would be 1.2, 0.2, and a few times, respectively.…”
Section: Economics Aspectmentioning
confidence: 99%
“…Typically, follower robots with one or multi on-board sensors are used to implement leader-follower strategies. Visionbased leader-follower systems have been widely used in convoy applications [23], [24], [25], [26]. By estimating the leader's position from the sequence of a video image, the follower is able to follow the leader [27], [28].…”
Section: Related Workmentioning
confidence: 99%
“…Estimation and tracking of bearing using directional antennas is the core of the proposed convoy system. A robot convoy team is composed into identical leader-follower pairs, as shown in Figure 2 [26]. The lead robot, on the right of the figure, is a mobile end node and guides a team in a robot convoy.…”
Section: B Problem Statementmentioning
confidence: 99%